2020
DOI: 10.1136/oemed-2020-106897
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early-stage silicosis through health screening of stone benchtop industry workers in Victoria, Australia

Abstract: ObjectivesThe popularity of high silica content artificial stone has been associated with emergence of severe, progressive silicosis as a major health issue affecting workers in the stone benchtop industry. This population-based health assessment programme has been implemented with the aim of identifcation of silica-associated disease at a preclinical stage.MethodsAll current and former workers from the stone benchtop industry in the State of Victoria are offered free health assessments. Primary evaluations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 27 publications
0
46
0
3
Order By: Relevance
“…This suspicion is reinforced by some studies; screening in ES workers in California has shown that 12% suffer from silicosis, diagnosed by chest radiology and ILO classification [ 52 ]. In addition, a more exhaustive evaluation in workers in Victoria (Australia) using chest radiology and HRCT showed that the percentage of patients with silicosis increased to 36% because HRCT detected cases with negative chest radiology [ 53 ]. If we consider that the number of exposed workers in the US is close to 100,000, we will have an idea of the magnitude of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…This suspicion is reinforced by some studies; screening in ES workers in California has shown that 12% suffer from silicosis, diagnosed by chest radiology and ILO classification [ 52 ]. In addition, a more exhaustive evaluation in workers in Victoria (Australia) using chest radiology and HRCT showed that the percentage of patients with silicosis increased to 36% because HRCT detected cases with negative chest radiology [ 53 ]. If we consider that the number of exposed workers in the US is close to 100,000, we will have an idea of the magnitude of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Those identified as ‘at risk of silicosis’ were referred to a respiratory physician for further evaluation including a high-resolution computed tomography (HRCT) chest scan. More details of the questionnaire and RHS methods are provided in an earlier paper ( Hoy et al , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…WorkSafe Victoria (WSV) funded respiratory health screening (RHS) for all past and present workers in benchtop fabrication businesses. Some preliminary silicosis findings from the first year of the registry have been published ( Hoy et al , 2020 ). This paper extends the earlier paper by looking at a larger group of workers.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure simulations indicate that working with ATH-containing synthetic countertops can lead to substantial airborne dust. In one set of simulated exposures, dust generated from cutting Corian™ was 32% in the respirable size range, contained 82% aluminium hydroxide, and had a respirable mass concentration as high as 1.52 mg/m 3 3 , 7 . A subsequent report using a similar simulated approach found that nearly twice as much of the dust produced (59%) was in the respirable range 8 .…”
Section: Introductionmentioning
confidence: 99%